EMPLOYMENT TERMINATION ISSUES WITH AN EMPLOYEE WHO IS A MEMBER OF THE TRADE UNION - Tarasova, Dace (Administrative and Criminal Justice, 2023)
The aim of the article is to state the main problems concerning employment termination with an employee who is a member of the trade union, and to work out the proposals on solutions of the problematic questions.Problems of termination of issues with and employee who is a member of the trade union are considered in the article. 110 clause the 1 part of the Labour Law determines that an Employer is prohibited to terminate Employment Contract with an Employee who is a member of the trade union if there is no preliminary agreement with a certain trade union. But 101 clause 6 part of the Labour Law determines that an Employer before termination of an Employment Contract has to clarify if an Employee is a member of the trade union. Therefore an Employer needs to ask the trade union for permission to terminate labour relationships with an Employee who is a member of the trade union.101 clause 7 paragraph determines, that an Employer has the right to terminate labour relationship with an Employee, when an Employee is not able to continue employment because of the state of health, and there is a certain medical statement. In this case, before termination of the Employment Contract an Employer has to ask the trade union for permission, but the trade union in this case is not competent enough, because the medical statement was issued by an authorized person. The Trade Union Law came into force in 2014, this Law does not consider the case that trade unions should be united according to the branches, occupations and other principles, that is why in reality Employees could participate in several trade unions or in one, which does not specialize in a certain branch or occupation. The problems also occur in the situations, when an Employee learns that an Employer wishes to terminate Employment Contract. In these situations Employee is looking for possible actions, in order to defence himself and joins the trade union, and becomes its member, and stays there till the problems are solved.